Determining In-situ Frequency Independent Attenuation and Complex Modulus of Pavement Materials using Wavelet Power Density of Vibration Method - Sri Atmaja P. Rosyidi (Widyagama University of Malang, 2022)
The features of vibration sources, site characteristics, the propagation of surface and body waves in the ground, and the reaction of structures are all important to consider when analyzing vibration-related issues, including those caused by traffic loading. Pavement vibration analysis can be used to determine the impact of damaging vibrations on the road and surrounding buildings or structures. Furthermore, this vibration can be utilized to calculate the dynamic properties of road pavement materials, such as the attenuation factor and damping ratio of the material, as well as the complex modulus of the pavement material. To minimize vibration damage, an environmental zone that is effective in reducing ground vibration amplitude is frequently used. However, estimating the degree of decrease in vibration amplitude at a given distance is challenging. In general, vibration attenuation with distance is made up of two components: geometric damping and material damping. Geometric damping is related to the qualities of the ground and the magnitude of the vibration, while material damping is dependent on the nature of the source of the vibration. The majority of ground vibrations are now monitored mainly at the ground surface, rather than in deep layers, and propagation patterns are not properly considered. The wavelet power density of vibration technique was used in this study to quantify the frequency-dependent attenuation of geometric damping at a variety of pavement structures in Malaysia and Indonesia. At each location, the energy in a seismic wave signal was calculated as a function of the Gaussian of the derivative wavelet in signal amplitude. The vibration source's propagating waves were described by examining the recorded particle motions and significant energy components in the time-frequency domain. The complex modulus of pavement materials was then calculated using the frequency-dependent attenuation factors. The results reveal that the wavelet power density of vibration method can properly define the physical properties of the dynamic pavement material, such as attenuation frequency, damping ratio, and complex pavement modulus. This approach has the advantages of being quick, cost-effective, and nondestructive.